The Effects of Dynamic Strategic Math on English Language Learners' Word Problem Solving. (August 2013) - Orosco, Michael J.; Swanson, H. Lee; O'Connor, Rollanda; Lussier, Cathy
English language learners (ELLs) struggle with solving word problems for a number of reasons beyond math procedures or calculation challenges. As a result, ELLs may not only need math support but also reading and linguistic support. The purpose of this study was to assess the effectiveness of a math comprehension strategy called Dynamic Strategic Math (DSM) on word problem solving for Latino ELLs. The strategy provides performance-contingent feedback based on the student's reading and language comprehension level. A multiple baseline design was used to assess 6 second-grade Latino ELLs at risk for math failure/math disability. As compared with the baseline phase, DSM increased word problem solving for all the participants. All students' level of performance was maintained during follow-up sessions. The results suggest the intervention facilitated math problem–solving performance.